Correction: Křížová et al. Fullerene Derivatives Prevent Packaging of Viral Genomic RNA into HIV-1 Particles by Binding Nucleocapsid Protein. Viruses 2021, 13, 2451 - Křížová, Ivana; Dostálková, Alžběta; Castro, Edison; Prchal, Jan; Hadravová, Romana; Kaufman, Filip; Hrabal, Richard; Ruml, Tomáš; Llano, Manuel; Echegoyen, Luis; Rumlová, Michaela (Viruses, 2022)
The authors wish to make the following corrections to this paper [...].